2019
DOI: 10.1007/s12355-019-00718-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variabilities and Genetic Gains for Yield Components in Regional Sugarcane Breeding Programmes on Réunion Island

Abstract: Sugarcane variety development programmes are costly and lengthy. It appears important to periodically assess their ability to select competitive genotypes for yield components and provide genetic gains. This article reports a 10-year retrospective analysis of successive variety trials conducted in four regional breeding programmes on Réunion Island in the most advanced regional selection stage. The four variety programmes were dedicated to the humid coastal zone (LM), the per-humid coastal zone (SB), the irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
2
14
0
3
Order By: Relevance
“…All yield and juice quality traits were negatively correlated with stem borer infestations except for fiber content (Table 2) in line of findings reported by different authors [39][40][41]. This shows that in stem borer infestations tended to increase fiber content of cane stalks.…”
Section: Phenotypic Correlations Between Pairs Of Agronomic Traitssupporting
confidence: 88%
“…All yield and juice quality traits were negatively correlated with stem borer infestations except for fiber content (Table 2) in line of findings reported by different authors [39][40][41]. This shows that in stem borer infestations tended to increase fiber content of cane stalks.…”
Section: Phenotypic Correlations Between Pairs Of Agronomic Traitssupporting
confidence: 88%
“…Sugarcane flowering impacted negatively on stalk internode number as exhibited by a correlation coefficient of -0.32***, while it enhanced cane and sugar yields with values of 0.28*** and 0.27*** respectively. The cane fiber content was correlated positively to internode number (0.42***) and stem borer infestations rate (0.30***), but negatively to cane yield (0.21***) as reported by different investigators [5,[40][41]. More importantly, it was not negatively correlated to the recoverable sucrose in contrast of findings obtained in the same agro-ecological context [42].…”
Section: Phenotypic Correlations Between Pairs Of Agro-morphological mentioning
confidence: 71%
“…From the literature, findings on heritability, genetic gain, PCV and GCV for the same traits look sometimes controversial depending on locations, crop cycle (plant cane or ratoon), soil types, water regime (rainfed or irrigated), etc. [6,22,40,59]. But still, this is all about the scope of experimentation in agronomy, findings being mostly site-specific.…”
Section: Heritability and Genetic Advancementioning
confidence: 99%
“…The estimated broad-sense heritability values indicate that the selection of clones for these trait based on phenotypic values would be effective since environment variance has shown little impact [48]. Ramos et al (2017) [49] found similar values of h 2 for FIB and PC.…”
Section: Discussionmentioning
confidence: 99%